Singapore Management University Report to Stakeholders 2020 - 2021 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2021)
Last year, the profound impact of the Covid-19 pandemic reaffirmed that the three strategic priorities we had identified for SMU and the wider community – digital transformation, sustainable living and growth in Asia – are the right priorities. As the world learns to manage Covid-19, focus must be given to sustainable living. Here SMU can contribute to driving solutions to manage climate change and sustainable city living.